1992
DOI: 10.1002/job.4030130103
|View full text |Cite
|
Sign up to set email alerts
|

The socialization of union loyalty

Abstract: The present study investigated the effects of a specific union socialization program on union attitudes and loyalty. Seventy-one apprentices undergoing a union-management training program were surveyed. Using linear structural relations modelling, the research found that union attitudes and training satisfaction were the most important predictors of loyalty to the union. Furthermore, attitudes to unions were related to the union socialization process and the transformational leadership characteristics of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 46 publications
(43 reference statements)
1
62
0
3
Order By: Relevance
“…Au cours des années, on a vu un nombre important d'études s'intéresser aux effets de ce type de leadership dans différents milieux organisationnels (Bass et Riggio, 2006), dont le milieu syndical (Cregan, Bartram et Stanton, 2009;Fullagar et al, 1994;Fullagar et al, 1992;Kelloway et Barling, 1993;Metochi, 2002;Twigg et al, 2007). Essentiellement, les leaders transformationnels se distinguent par leur capacité à « elevates the follower's level of maturity, ideals, and concerns for the well-being of others, the organization, and society » (Bass et Bass, 2008 : 619).…”
Section: Le Leadership Transformationnel Et L'engagement Syndicalunclassified
“…Au cours des années, on a vu un nombre important d'études s'intéresser aux effets de ce type de leadership dans différents milieux organisationnels (Bass et Riggio, 2006), dont le milieu syndical (Cregan, Bartram et Stanton, 2009;Fullagar et al, 1994;Fullagar et al, 1992;Kelloway et Barling, 1993;Metochi, 2002;Twigg et al, 2007). Essentiellement, les leaders transformationnels se distinguent par leur capacité à « elevates the follower's level of maturity, ideals, and concerns for the well-being of others, the organization, and society » (Bass et Bass, 2008 : 619).…”
Section: Le Leadership Transformationnel Et L'engagement Syndicalunclassified
“…Individual attitudes to unions in general have been found to have an important moderating or 'gate-keeping' role in the unionization process, being related to union joining, commitment and participation (Fiorito and Young 1998;Fullagar et al 1992;Kelloway et al 1997). We find that younger New Zealand workers hold no less positive attitudes to trade unions in general than their older counterparts.…”
Section: Attitudes Of Younger and Older Workers Comparedmentioning
confidence: 99%
“…Another study by Tannenbaum, Mathieu, Salas and Cannon-Bowers (1991) found that the extent to which training fulfills a trainee's expectations or desires was positively related to post-training organizational commitment. Additionally, in a study of socialization in unions, Fullagar, McCoy and Shull (1992) found that satisfaction with training was an important predictor of loyalty to the union. Note that most of the studies which found significant positive relationships with training used measures which were evaluations of training made by the employee.…”
Section: Training Correlates and Implications For Hrmmentioning
confidence: 99%